Think tanks, policy networks and education governance: The rising of new intra-national spaces of policy in Portugal - Viseu, Sofia (2018)
This article focuses on the role of think tanks in education governance in Portugal, We are interested in contributing to a literature that discusses the emergence of new intra-national spaces of policy, and examines how the actors operating in those spaces work and influence education policy. This article is based on an empirical study conducted by EDULOG, a think tank for education that has been operating since 2015. We mapped EDULOG’s activities, the information generation activities, organizations, and actors connected to EDULOG using a network ethnography and social network analysis. This study shows that a) this organization articulated a network of actors from different sectors, including the academy, business and government agencies; and b) EDULOG acts as a space of social and cognitive intermediation, committed to developing knowledge geared towards policy decision and problem solving.